Legal Protection for Copyright Owners Against Book Piracy at Diponegoro Stadium in Semarang: Perlindungan Hukum bagi Pemilik Hak Cipta Terhadap Pembajakan Buku di Stadion Diponegoro Semarang - Hendika, Billy Auliadi (Annual Review of Legal Studies, 2024)
This research aims to explore the aforementioned issues from a legal standpoint, with the following objectives: (1) to comprehend and analyze the perceptions of book buyers towards duplicated books through photocopying concerning the economic rights of book creators in Semarang city, and (2) to understand and analyze the perceptions of book sellers towards duplicated books through photocopying in terms of the economic rights of book creators in Semarang. The study adopts a juridical-empirical method with a qualitative approach, offering insights into the current situation in the field related to legal regulations, particularly Law Number 28 of 2014 concerning Copyright. The research findings and discussions reveal the following points: (1) Based on respondents' statements, copyright protection for creators' work is crucial as it ensures the originality of ideas/concepts. Such protection grants creators a sense of security and enables them to fully exercise their economic and moral rights. However, respondents still opt for pirated books due to their significantly lower prices compared to genuine ones, albeit with the trade-off of lower paper quality. (2) Businesses sell pirated books because not everyone in society enjoys favorable economic conditions. Additionally, a majority of Semarang residents prioritize the content of books over their physical quality. The substantial price difference between pirated and genuine books may render the latter unaffordable for some individuals, prompting businesses to facilitate access to knowledge for the community through the sale of pirated books.